2022
DOI: 10.1021/acscentsci.1c01479
|View full text |Cite
|
Sign up to set email alerts
|

The First-in-Human Synthetic Glycan-Based Conjugate Vaccine Candidate against Shigella

Abstract: Shigella , the causative agent of shigellosis, is among the main causes of diarrheal diseases with still a high morbidity in low-income countries. Relying on chemical synthesis, we implemented a multidisciplinary strategy to design SF2a-TT15, an original glycoconjugate vaccine candidate targeting Shigella flexneri 2a (SF2a). Whereas the SF2a O-antigen features nonstoichiometric O-acetylation, SF2a-TT15 is made of a synthetic 15mer oligosaccharide, corresponding to three non-O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 71 publications
(173 reference statements)
0
28
0
Order By: Relevance
“…Previous studies have found that O -acetylation had an impact on the immunogenicity of isolated meningococcal and Salmonella typhi vaccines, whereas in contrast for others such as the semisynthetic Shigella vaccines, no effect of acetylation was observed. 89 93 We found that both acetylated ( 1 through 4 ) and the nonacetylated antigen 53 elicited IgG responses with functional activity against E. coli , suggesting that for this particular antigen, acetyl groups may have a limited effect on immunogenicity. Overall, the binding studies with the mAbs suggest that an O25B glycoconjugate vaccine elicits IgGs characterized by heterogeneous epitope recognition patterns.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have found that O -acetylation had an impact on the immunogenicity of isolated meningococcal and Salmonella typhi vaccines, whereas in contrast for others such as the semisynthetic Shigella vaccines, no effect of acetylation was observed. 89 93 We found that both acetylated ( 1 through 4 ) and the nonacetylated antigen 53 elicited IgG responses with functional activity against E. coli , suggesting that for this particular antigen, acetyl groups may have a limited effect on immunogenicity. Overall, the binding studies with the mAbs suggest that an O25B glycoconjugate vaccine elicits IgGs characterized by heterogeneous epitope recognition patterns.…”
Section: Discussionmentioning
confidence: 83%
“…The original synthesis of SF2a-TT15 was scaled up successfully. A GMP batch was produced [ 11 ]. SF2a-TT15 GMP was immunogenic in rabbits and passed all toxicity criteria [ 11 ].…”
Section: From Polysaccharide Antigens To Sf2a-tt15 a Shigel...mentioning
confidence: 99%
“…A GMP batch was produced [ 11 ]. SF2a-TT15 GMP was immunogenic in rabbits and passed all toxicity criteria [ 11 ]. Moreover, SF2a-TT15-induced sera in mice recognized a large panel of SF2a strains circulating worldwide [ 11 ].…”
Section: From Polysaccharide Antigens To Sf2a-tt15 a Shigel...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fully synthetic antigens reached the clinic by the synthetic Haemophilus influenzae type b (Hib) vaccine in Cuba, 18 and more recently a vaccine to fight shigellosis has progressed to phase II clinical trials. 19,20 The use of synthetic glycans with modern structural glycobiology approaches, such as glycan arrays, X-ray crystallography, surface plasmon resonance, and saturation transfer difference NMR, can nowadays be used for rational rather than trial-and-error-based glycoconjugate vaccine design. 21,22 This review aims at discussing the advancement of glycoconjugate vaccines based on synthetic carbohydrates to improve existing vaccines and identify novel candidates to combat AMR.…”
Section: Introductionmentioning
confidence: 99%